An STM study of surface structures on WO3(001) - Jones, F; Rawlings, K; Foord, J; Egdell, R; Pethica, J; Wanklyn, B; Parker, S; Oliver, P (1996)
Structure on the (001) surface of monoclinic WO3 has been studied by scanning tunnelling microscopy. Electrostatic instability at the polar surface of WO3(001) is avoided by termination of the outer WO2 layer with half a monolayer of oxygen ions to produce a (√2 × √2)R45° arrangement of on-top oxygen. An additional periodicity is introduced in some terrace areas by tilting of WO6 octahedra to produce alternately long and short on-top O-O separations along the [110] direction. This produces a (2×2) superstructure approximating to the space group c2mm. Prominent defect troughs on oxygen annealed surfaces are attributed to missing oxygen ions. Topographically resolved I-V curves show that significant filled state electron density resides in the trough bottoms. Argon ion bombardment and subsequent annealing leads to the appearance of defects in which on-top oxygen is removed from adjacent W ions to generate linear features three unit cells wide running along the [100] direction. These new defects aggregate with the troughs to produce characteristic branched structures. Prolonged bombardment and annealing leads eventually to large terrace areas displaying a new (2 × 2) superstructure in which only a 1/4 of the W ions carry on-top oxygen.